Laparoscopic distal gastrectomy for synchronous adenocarcinoma, diffuse large B cell lymphoma and gastrointestinal stromal tumor in the stomach: a case report - Toshiyasu Ojima; Hirotaka Tabata; Hiroki Yamaue (Surgical Case Reports, 2022)
Abstract Background Synchronous lymphoma and adenocarcinoma are occasionally detected in the stomach. Gastrointestinal stromal tumor (GIST) and adenocarcinoma are sometimes seen simultaneously in the stomach. However, we rarely observe synchronous adenocarcinoma, lymphoma, and GIST in the stomach, and there are few reports on cases with these three lesions. Case presentation This is a case report of a 71-year-old man who had a laparoscopic distal gastrectomy and lymphadenectomy for three gastric tumors. Preoperative diagnoses were early adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma in the stomach, but final diagnosis was synchronous adenocarcinoma, diffuse large B cell lymphoma (DLBCL), and GIST. Helicobacter pylori (H. pylori) is highly involved in the development of DLBCL and MALT lymphoma in the stomach. Gastric adenocarcinoma is partially involved in chronic gastritis with atrophy and intestinal metaplasia caused by H. pylori infection. Indeed, a rapid urease test was found positive in this case. Therefore, we prescribed medicine to eliminate H. pylori after gastrectomy. Conclusion This is the first case report where a patient underwent minimally invasive laparoscopic gastrectomy for synchronous adenocarcinoma, DLBCL and GIST in the stomach, although one patient who underwent open gastrectomy for synchronous adenocarcinoma, MALT lymphoma and GIST was previously reported.